Risk factors influencing curative effect of class Ⅳ lupus nephritis - ZHANG Yu-rong; QI Yuan-yuan; MA Xiao; MENG Rui-xia; YANG Yan; WANG Jing (Linchuang shenzangbing zazhi)
Objective To investigate the clinical risk factors for unresponsive common approaches on the treatment of class IV lupus nephritis(LN).Methods The class IV LN patients were confirmed by renal biopsy,treated with glucocorticoid and common immunosuppressive agents and followed up for more than6 months.They were divided into two groups according to curative effect after treatment for 6months.The differences between the two groups were analyzed by means of demographic characteristics,clinical manifestations,laboratory tests,autoantibodies,pathologic indicators,treatment regimens and outcomes.The possible influencing risk factors on the classⅣ LN were analyzed by Kaplan-Meier,and the independent risk factors were analyzed by multivariate COX regression modeling.Results A total of 198 patients with complete data and regularly followed-up were enrolled.They were divided into two groups:50(25.25%)patients in non-response group and 148(74.75%)in response group.There was no significant difference between two groups in responsive rate under various common induction therapies.And then,the risk factors influencing the curative effects of class LN Ⅳ patients were further explored.Results showed that the nonresponse group had a higher rate of photosensitization,renal dysfunction,moderate proteinuria,the anti-RNP positive,renal glomerular sclerosis,CI,chronic interstitial lesions,interstitial cellular infiltration and NNV than in the response group(P<0.05).Kaplan-Meier results showed that a decreasing response happened in the group with a higher rate of renal dysfunction,chronic lesions and interstitial cellular infiltration(Log Rank P<0.05).Then multivariate COX regression model investigated that renal dysfunction was an independent risk factor for poor curative effect.Conclusions Under the treatment of common induction therapy,the classⅣ LN patients with baseline renal dysfunction have a terrible curative effect.In addition,it is possible that the baseline anti-RNP positivity,chronic interstitial lesions,interstitial cellular infiltration or NNV are the risk factors for unresponsive treatment.